2011
DOI: 10.1111/j.1365-2559.2011.03861.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunophenotypic features of testicular tumour of the adrenogenital syndrome

Abstract: In addition to clinical information, biochemical profile and histopathological findings, our results suggest that immunohistochemistry using a panel of antibodies including CD56, synaptophysin and androgen receptor is helpful in differentiating TTAGS from LCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
0
30
1
2
Order By: Relevance
“…Surgery is also suggested if an LC neoplasm is suspected, as the majority of LCT cases in this age group are benign. Few studies investigated immunohistochemical profiles of TART and LCT, and the currently available markers include synaptophysin, CD56 (both stronger in TART than in LCT) and the androgen receptor (absent in TART but positive in most cases of LCT) (24,25). A recent study, published after our study had been submitted for publication, investigated classical markers of steroidogenesis at mRNA level, and found most markers expressed in TART (10).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is also suggested if an LC neoplasm is suspected, as the majority of LCT cases in this age group are benign. Few studies investigated immunohistochemical profiles of TART and LCT, and the currently available markers include synaptophysin, CD56 (both stronger in TART than in LCT) and the androgen receptor (absent in TART but positive in most cases of LCT) (24,25). A recent study, published after our study had been submitted for publication, investigated classical markers of steroidogenesis at mRNA level, and found most markers expressed in TART (10).…”
Section: Discussionmentioning
confidence: 99%
“…Immunostains may also be of assistance; the adrenogenital "tumor" frequently shows significant reactivity for CD56 and synaptophysin and is negative for androgen receptor, with Leydig cell tumor showing an opposite pattern of immunoreactivty. 231,232 Cystic dysplasia This is a rare lesion associated with ipsilateral renal agenesis and may cause a testicular mass in childhood, with a median age of presentation of 3 years, although patients may present at any time from the neonatal period to adult life. 233 These lesions are felt to arise because of failure of development of the normal mesonephric tubules, leading to defective or absent connection of the rete testis with the efferent ductules of the epididymis.…”
Section: Tumor-like Lesions Of the Testismentioning
confidence: 99%
“…Current immunohistochemical summary data predict that 85–95% of LCTs will show immunoreactivity for inhibin, Mart-1, and calretinin [7]. Two small series have shown that <10% of LCTs will show strong immunoreactivity for synaptophysin [8, 9]. …”
Section: Introductionmentioning
confidence: 99%